Heavy metals zinc, cadmium, and copper stimulate pulmonary sensory neurons via direct activation of TRPA1 - Gu, Qihai (American Physiological Society, 2010)
Airway exposure to zinc dust and zinc-containing ambient particulates can cause symptoms of airway irritation and inflammation, but the underlying molecular and cellular mechanisms are largely unknown. Transient receptor potential A1 (TRPA1) is selectively expressed in a subpopulation of pulmonary C-fiber afferents and has been considered as a major irritant sensor in the lung and airways. Using whole cell patch-clamp recording and Ca(2+) imaging, we have demonstrated that application of ZnCl(2) concentration dependently evoked inward current and Ca(2+) transient in isolated vagal pulmonary sensory neurons; both responses were almost completely inhibited after pretreatment with AP18, a specific TRPA1 antagonist. In anesthetized spontaneously breathing animals, intratracheal instillation of ZnCl(2) (2 mM, 25 μl) induced pronounced respiratory depression in wild-type mice, and the effect was essentially absent in TRPA1-deficient mice. In addition, our study showed that two other heavy metals, cadmium and copper, also stimulated pulmonary sensory neurons via a direct activation of TRPA1. In summary, our results suggest that activation of TRPA1 in pulmonary C-fiber sensory nerves may contribute to the respiratory toxicity induced by airway exposure to these three heavy metals.